2007
DOI: 10.1038/sj.ijo.0803530
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions associated with body mass index in Canadian adults

Abstract: Objective: To examine the associations between excess weight and health-care utilization in general Canadian population. Design: A national survey with a multistage stratified sampling design. Subjects: A total of 113 603 adults 20 years of age or more in 2003. Measurements: Self-reported overnight stay as an in-patient during the past 12 months, length of stay, height and weight.Results: The 12-month cumulative incidence of being an in-patient was 6.6% for men and 10.4% for women, with the length of stay in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
(41 reference statements)
1
23
1
Order By: Relevance
“…One such report [4] estimated that obesity accounted for up to 2.8% of healthcare expenditure globally but concluded that this was likely to be an underestimate. Although some studies have looked directly at the relationship between BMI and hospital admission rates [6-14], relatively few have considered duration of stay [6-8,10] and most have had insufficient power to assess reliably the relationship between BMI and less common causes of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…One such report [4] estimated that obesity accounted for up to 2.8% of healthcare expenditure globally but concluded that this was likely to be an underestimate. Although some studies have looked directly at the relationship between BMI and hospital admission rates [6-14], relatively few have considered duration of stay [6-8,10] and most have had insufficient power to assess reliably the relationship between BMI and less common causes of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Again, this study did not present any information on the medical characteristics and the HRQoL of this population, thus offering an incomplete picture of the burden of obesity in Ontario. While other Canadian studies have shown that obese individuals were more likely to have medical conditions, to report a worse HRQoL than normal-weight individuals and to consume more medical resources,57 these studies were limited as they did not include the elderly6 or all BMI categories (eg, overweight) 7. There is also a lack of data on the Canadian costs associated with being underweight 8…”
Section: Introductionmentioning
confidence: 99%
“…Results have been mixed, with some studies finding positive associations between obesity and hospital admissions79,1113,15,16,18,19 and others finding no association10,14 or negative association. 17 Studies measured the effect of obesity on the risk of hospitalizations,7,9,10,1214,17,18 length of hospital stay,8,9,11,16,19 or avoidable risk of hospitalizations and stays 15. Only three studies measured the effect of obesity on the number of hospitalizations 9,11,16…”
Section: Introductionmentioning
confidence: 99%